1993
DOI: 10.1002/j.1460-2075.1993.tb05999.x
|View full text |Cite
|
Sign up to set email alerts
|

A dominant negative mutant of 2-5A-dependent RNase suppresses antiproliferative and antiviral effects of interferon.

Abstract: 2‐5A‐dependent RNase is the terminal factor in the interferon‐regulated 2‐5A system thought to function in both the molecular mechanism of interferon action and in the general control of RNA stability. However, direct evidence for specific functions of 2‐5A‐dependent RNase has been generally lacking. Therefore, we developed a strategy to block the 2‐5A system using a truncated form of 2‐5A‐dependent RNase which retains 2‐5A binding activity while lacking RNase activity. When the truncated RNase was stably expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
173
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(178 citation statements)
references
References 52 publications
(45 reference statements)
4
173
0
Order By: Relevance
“…RNase L was initially proposed to be a candidate tumor suppressor by us and Peter Lengyel based on its involvement in the antiproliferative activity of IFN and on the location of RNASEL at chromosome 1q25, a region deleted or rearranged in some breast cancers [89][90][91]. However, specific evidence of a role for RNase L in the suppression of cancer had to wait almost 10 years, until the long sought, hereditary prostate cancer 1 (HPC1) was mapped to the RNase L gene by the group of Jeff Trent [92].…”
Section: The Role Of Rnase L In Hereditary Prostate Cancer and Discovmentioning
confidence: 99%
“…RNase L was initially proposed to be a candidate tumor suppressor by us and Peter Lengyel based on its involvement in the antiproliferative activity of IFN and on the location of RNASEL at chromosome 1q25, a region deleted or rearranged in some breast cancers [89][90][91]. However, specific evidence of a role for RNase L in the suppression of cancer had to wait almost 10 years, until the long sought, hereditary prostate cancer 1 (HPC1) was mapped to the RNase L gene by the group of Jeff Trent [92].…”
Section: The Role Of Rnase L In Hereditary Prostate Cancer and Discovmentioning
confidence: 99%
“…In addition to a role in mediating resistance to virus infection, the 2-5A system is also implicated in the control of cell growth and proliferation (Williams and Silvermann, 1985). Overexpression of the wild-type 2-5A synthetase gene inhibits cell proliferation (Rysiecki et al, 1989), while overexpression of catalytically inactive mutants of RNase L renders cells resistant to the antiviral and antiproliferative e ects of IFNs (Hassel et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 RNase L plays a central role in IFNs cell growth inhibition and in IFN-induced apoptosis. [8][9][10][11][12] Activation of RNase L causes caspase-dependent apoptosis accompanied by cytochrome c release from the mitochondria. [13][14][15] Moreover, we have shown that part of RNase L is localized in mitochondria and regulates mitochondrial mRNA stability in IFNa-treated cells.…”
mentioning
confidence: 99%